If we assess, will they learn? Students’ perspectives on the complexities of assessment-for-learning (Canadian Medical Education Journal, 2023)
Introduction: Assessment can positively influence learning, however designing effective assessment-for-learning interventions has proved challenging. We implemented a mandatory assessment-for-learning system comprising a workplace-based assessment of non-medical expert competencies and a progress test in undergraduate medical education and evaluated its impact.Methods: We conducted semi-structured interviews with year-3 and 4 medical students at McGill University to explore how the assessment system had influenced their learning in year 3. We conducted theory-informed thematic analysis of the data.Results: Eleven students participated, revealing that the assessment influenced learning through several mechanisms. Some required little student engagement (i.e., feed-up, test-enhanced learning, looking things up after an exam). Others required substantial engagement (e.g., studying for tests, selecting raters for quality feedback, using feedback). Student engagement was moderated by the perceived credibility of the system and of the costs and benefits of engagement. Credibility was shaped by students’ goals-in-context: becoming a good doctor, contributing to the healthcare team, succeeding in assessments.Discussion: Our assessment system failed to engage students enough to leverage its full potential. We discuss the inherent flaws and external factors that hindered student engagement. Assessment designers should leverage easy-to-control mechanisms to support assessment-for-learning and anticipate significant collaborative work to modify learning cultures.